„Rossica” jako środek opisu i interpretacji życia politycznego we współczesnej Polsce - Sarnowski, Michał (Studia Rossica Posnaniensia, 2015)
This article is an attempt to show the interesting way in which the Polish press describes and interprets contemporary political life in Poland by making various allusions (i.e. references) to history and participants in current political life in Russia.